مدارس تقصيد الأحكام الشرعية - Nasreddine, Adjdir (Jurnal Studi Al-Qur'an, 2019)
ملخص البحث إن معرفة قصد الشارع من سوق الأحكام أمر مهم يتوجب على الناظر أن يدركه ادراكا موافقا لما رامه الشارع، و لقد تعدد آراء النظار باستصحاب خلفيتهم الفكرية والعقدية وعليه تمايزت جملة من المدارس في النظر للنصوص القرآنية وبيان مراد الله منها. في هذا البحث تذكر ثلاث أنواع من المدارس: الباطنية، الظاهرية،جمهور. تعتمد هذا البحث على المنهج الوصفي و تحتوي على ثلات الامباحث.من أهم النتائج يتجلى أن للخلفية العقدية والفكرية أثر في بيان المراد وابداء التفسير وفق ما يخدم المنهج والفكر المعين للمتقصد. فن المقاصد من العلوم التي ترفع لنا الخلاف الواقع والمتوقع والمشتبه . الكلمات المفتاحة: مدارس مقاصد، أحكام، النظر Abstact Knowing the purpose of the sharia or judgments is important that the beholder should be aware of in accordance with what was thrown on judgments, and the views of the principals were accompanied by their intellectual and ideological background and therefore differentiated a number of schools in the consideration of the Quranic texts and the statement of The God. In this research mentioned three types of schools: Batiniyyah, Dohiriyan, and Jumhur or in another name call Ahlu Sunnah. This research-based on descriptive approach and contains the three parts of the researcher. The most important results are the background of the faith or theology ideology and intellectual effect in the statement of intent and the interpretation of what serves the curriculum and thought specific to the intended. The art of intents of science that raise us disagreement reality, expected and suspected. Keywords: Maqasid School, Judgments, Sharia